Germinability of annual bluegrass seed during spring in the Eastern United States. Issue 2 (12th August 2021) - Carroll, Devon E.; Brosnan, James T.; McCurdy, James D.; De Castro, Edicarlos B.; Patton, Aaron J.; Liu, Wenwen; Kaminski, John E.; Tang, Kaiyuan; McCullough, Patrick E.; Westbury, David
Abstract: Soil seedbank management via collecting clippings may be a means of combatting herbicide resistance in annual bluegrass ( Poa annua L.) by minimizing recruitment from the deposition of viable seed into the soil. Our objective was to assess the germinability of annual bluegrass seed in spring to determine when collecting clippings would be most impactful. Research was conducted across 2019 and 2020 in five locations: Knoxville, TN; Starkville, MS; Griffin, GA; West Lafayette, IN; and University Park, PA. Annual bluegrass seed was harvested every 100 growing degree‐days (GDD0C ; base 0 °C with accumulation beginning on 1 January each year from 400 to 1, 100 GDD0C . Seeds from each harvest timing were placed on moistened blotter paper in petri dishes and randomized in a growth chamber set to a 77:68 °F and 8:16 h light–dark cycle. Germination was assessed every 3 d until 21 d of incubation. Cumulative germination percentage after 21 d of incubation increased at research locations in northern latitudes. In Tennessee, germination was greatest from 600 to 900 GDD0C . In Indiana, germination did not exceed 50% until 600 GDD0C and increased with GDD0C accumulation. Clippings should not be collected until at least 600 GDD0C in these locations. In Pennsylvania, little variation existed among GDD0C harvest times, indicating that clipping collection may be a valuable practice any time mature seedheads are present. Turfgrass managers should consider geographic location when selecting a time to implement clipping collections and will probably need to conduct multiple clipping collection events. Core Ideas: Growing degree‐day accumulation influenced Poa annua seed germinability. Poa annua seed harvested in spring had greater germinability in northern locations. The optimum clipping collection time to prevent seed rain varied by location.